2019
DOI: 10.1016/j.bjorl.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of resection margin in open oncologic laryngeal surgery: survival analysis of a cohort of 139 patients affected by squamous cell carcinoma

Abstract: Our study did not recognize resection margin as an independent prognostic factor; most previously published papers lack unanimous, methodological choices, and the cohorts of patients analyzed are not easy to compare. To reach a unanimous agreement regarding the prognostic value of resection margins, it would be necessary to carry out meta-analyses on studies sharing definition of resection margin, methodology and post-operative therapeutic choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Consistent with previous studies, margin status was found to have a significant association with survival among patients with LSCC in the present study [29, 30]. Published trials about LSCC did not report that tumor status was an independent risk factor for OS.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, margin status was found to have a significant association with survival among patients with LSCC in the present study [29, 30]. Published trials about LSCC did not report that tumor status was an independent risk factor for OS.…”
Section: Discussionsupporting
confidence: 91%
“…TTTY14 (testis-specific transcript, Y-linked 14) was thought to be associated with human papillomavirus (HPV) induced tumorigenesis, the expression level of TTTY14 was obsearvedly differed between HPV inactive/negative group and HPV active group [28], in accordance with our functional enrichment analysis. In additional, TTTY14 was identified as significantly correlated with overall survival in OSCC and gastric cancer [26,27] Consistent with previous studies, margin status was found to be significant association with survival among patients with LSCC in the present study [29,30]. Published trials about LSCC did not reported that tumor status which was an independent risk factor for OS in our study was related to prognosis of LSCC.…”
Section: Rp11-169k164 and Rp11-107e53 To Predict Recurrence Of Patsupporting
confidence: 90%
“…Most patients are men. Typically, the ratio for men is 4:1, and the ratio for women is 20:1 (4). The application of more therapeutic methods and treatment concepts has greatly improved in the past decade, and the incidence of LSCC has decreased.…”
Section: Introductionmentioning
confidence: 99%